Rodenticide Causing Lower Gastrointestinal Bleeding: Resident Simulation - Rohit B. Sangal; Lauren W. Conlon (Association of American Medical Colleges, 2018)
Introduction Gastrointestinal (GI) bleeding is becoming more common with an aging population. Lower GI bleeding is less common than its upper GI bleed counterpart. Incidence of bleeding is increasing because more patients are on anticoagulation medication. Abnormal coagulation can lead to this life-threatening condition requiring rapid diagnosis and treatment by a skilled medical provider. Simulation can be used to practice recognition of this disease process and work through treatment algorithms. Methods This simulation case used a high-fidelity simulator to teach emergency medicine providers how to manage lower GI bleeding in a patient with abnormal coagulation secondary to intentional ingestion of rodenticide. The case simulated a 58-year-old female with history of bipolar disorder presenting with brisk rectal bleeding. Residents were expected to identify the type of GI bleed, leading to recognition that the patient was in hemorrhagic shock; they then had to appropriately reverse the anticoagulation and resuscitate with blood products. Afterward, learners were given a short survey to evaluate the case and debriefing process. Results The case was performed at the University of Pennsylvania Simulation Center as part of the Emergency Medicine Resident Simulation Curriculum. Twenty-eight learners took part; of these, 20 (71%) found the simulation realistic, and 24 (86%) agreed or strongly agreed that the simulation was useful. Discussion Main learning points include management of lower GI bleeding and reversal of abnormal anticoagulation. This simulation case is straightforward to run, requires minimal resources, and has been well received by learners at our institution.